2016
DOI: 10.1038/srep38979
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroartemisinin inhibits catabolism in rat chondrocytes by activating autophagy via inhibition of the NF-κB pathway

Abstract: Osteoarthritis is a disease with inflammatory and catabolic imbalance in cartilage. Dihydroartemisinin (DHA), a natural and safe anti-malarial agent, has been reported to inhibit inflammation, but its effects on chondrocytes have yet to be elucidated. We investigated the effects of DHA on catabolism in chondrocytes. Viability of SD rats chondrocytes was analyzed. Autophagy levels were determined via expression of autophagic markers LC3 and ATG5, GFP-LC3 analysis, acridine orange staining, and electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 33 publications
4
32
1
Order By: Relevance
“…In addition, several groups have reported that the expression of CXCL-1 was increased after ATG5 silencing in chondrocytes, and autophagy can increase the recruitment of PMNs in lung tissue after 3-MA and CQ treatment. 31,32 Consistent with our expectation, the production of CXCL-1 and the recruitment of PMNs were markedly enhanced after autophagy inhibition compared with infected control group, whereas rapamycin treatment reduced the expression of CXCL-1 and the recruitment of PMNs, which suggested that autophagy can reduce the recruitment of PMNs in A. fumigatus keratitis. Interestingly, as we detected the euchromatin fraction of the nucleus and the number of granules per cytoplasm area in corneas of mice by TEM analysis, we observed that the morphology of PMNs was changed in corneas with 3-MA and CQ treatment, indicating that autophagy may play an essential role in activation, differentiation, and antibacterial ability of neutrophil.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, several groups have reported that the expression of CXCL-1 was increased after ATG5 silencing in chondrocytes, and autophagy can increase the recruitment of PMNs in lung tissue after 3-MA and CQ treatment. 31,32 Consistent with our expectation, the production of CXCL-1 and the recruitment of PMNs were markedly enhanced after autophagy inhibition compared with infected control group, whereas rapamycin treatment reduced the expression of CXCL-1 and the recruitment of PMNs, which suggested that autophagy can reduce the recruitment of PMNs in A. fumigatus keratitis. Interestingly, as we detected the euchromatin fraction of the nucleus and the number of granules per cytoplasm area in corneas of mice by TEM analysis, we observed that the morphology of PMNs was changed in corneas with 3-MA and CQ treatment, indicating that autophagy may play an essential role in activation, differentiation, and antibacterial ability of neutrophil.…”
Section: Discussionsupporting
confidence: 85%
“…The same effect was also observed in DHA‐treated chondrocytes, in which DHA treatment attenuated TNF‐α‐stimulated nuclear translocation and the degradation of p65 and IκBα, indicating NF‐κB inhibition. This inhibition then resulted in the induction of autophagy by DHA . Furthermore, Hu et al reported that, in many cancer cell types, including RPMI 8226, NB4, HCT116, and HeLa cells, DHA induces autophagy through the inhibition of NF‐κB activity.…”
Section: Signaling Pathways and Cellular Targets Involved In Autophagsupporting
confidence: 62%
“…99,100 DHA treatment leads to the inhibition of NF-κB activity through blocking RelA/p65 translocation to the nucleus and has a significant repressive effect on the phosphorylation and degradation of IκBα in cancer cells. 48,101 The same effect was also observed in DHA-treated chondrocytes, 102 that further stimulated autophagy. 48 Further evidence showed that DHA-induced autophagy sensitizes some chemotherapeutics, highlighting the role of autophagy as the inducer of cancer cell death.…”
Section: The Ampk Pathwaysupporting
confidence: 55%
See 1 more Smart Citation
“…The optical density was measured using a SpectraMax 190 microplate reader (Molecular Devices, Sunnyvale, CA) at 450 nm. Cell viability was calculated as previously described …”
Section: Methodsmentioning
confidence: 99%